Clinical-epidemiological evaluation of respiratory syncytial virus infection in children attended in a public hospital in midwestern Brazil - Calegari,Tatiany (2005)
Respiratory syncytial virus (RSV) is responsible for annual respiratory infection outbreaks in infants and young children worldwide, frequently causing bronchiolitis and pneumonia. We evaluated clinical and epidemiological features of acute respiratory infections (ARIs) caused by respiratory syncytial virus (RSV) in children less than five years old. Nasopharyngeal aspirate samples from children with ARI symptoms, attended at the 'Hospital das Clínicas' - Federal University of Uberlândia, MG, Brazil, were collected and tested for RSV by the immunofluorescence assay (IFA). Patients' clinical and epidemiological data were also obtained. From April 2000 to June 2003, 317 nasopharyngeal samples were collected from children less than 54 months old. Seventy-six samples (24.0%) were positive for RSV, with 53% (40/76) obtained from male patients. Hospitalization occurred in 50% (38/76) of the cases, with an average period of 10.6 days, in most cases (87%, 33/38) occurring in children less than 12 months of age. Although an association between this age group and the presentation of more severe clinical symptoms was observed, such as bronchiolitis in 51% (27/53) of the patients and pneumonia in 19% (10/53), no patients died. RSV was found from February to August, with the highest incidence in May. Conclusions: RSV is an important agent that causes ARIs; the clinical manifestations varied from mild to severe and patients frequently required hospitalization; RSV mostly affected children less than one year old.